Advances in microalgal research for valorization of industrial wastewater. (January 2022) - Maurya, Rahulkumar; Zhu, Xinyu; Valverde-Pérez, Borja; Ravi Kiran, Boda; General, Thiyam; Sharma, Suvigya; Kumar Sharma, Anil; Thomsen, Marianne; Venkata Mohan, S.; Mohanty, Kaustubha; Angelidaki, Irini
Graphical abstract: Highlights: Industrial wastewater (IWW) serve as ideal nutrient growth media for microalgae. IWW requires specific pretreatments and optimization before microalgae cultivation. Recent advances of IWW treatments through microalgae cultivation are explored. Microalgal biomass grown on IWWs must be valorized to value-added products. Abstract: This review article focuses on recent updates on remediation of industrial wastewater (IWW) through microalgae cultivation. These include how adding additional supplements of nutrient to some specific IWWs lacking adequate nutrients improving the microalgae growth and remediation simultaneously. Various pretreatments strategy recently employed for IWWs treatment other than dealing with microalgae was discussed. Various nutrient-rich IWW could be utilized directly with additional dilution, supplement of nutrients and without any pretreatment. Recent advances in various approaches and new tools used for cultivation of microalgae on IWW such as two-step cultivation, pre-acclimatization, novel microalgal-bioelectrical systems, integrated catalytic intense pulse-light process, sequencing batch reactor, use of old stabilized algal-bacterial consortium, immobilized microalgae cells, microalgal bacterial membrane photobioreactor, low-intensity magnetic field, BIO_ALGAE simulation tool, etc. are discussed. In addition, biorefinery of microalgal biomass grown on IWW and its end-use applications are reviewed.